The Future of EU-Russia Energy Relations in the Context of Decarbonisation. Issue 4 (1st October 2016) - Khrushcheva, Olga; Maltby, Tomas
ABSTRACT: In 2013, there was a joint commitment to "long term strategic EU-Russia energy cooperation". 1 Whilst centred on oil and gas, it is noted that "the importance of renewables for EU-Russia energy relations should grow too", 2 and that for energy efficiency, "cooperation potential is immense and could… contribute to the objective of a Pan-European energy area". 3 Given this shared objective, this article analyses EU and Russian energy decarbonisation policy objectives and considers the potential for a supplementary trade relationship based on renewable energy flows and decarbonisation-related technology, as well as the implications for existing energy trade. Despite declarative statements of mutual interest, shared objectives and cooperation in decarbonisation policy, there has been very limited cooperation by early 2016. The EU has set ambitious plans to decarbonise its economy and energy sector by 2050. However, in Russia energy policy is dominated by hydrocarbon exports, decarbonisation targets are modest, and there are major problems with their implementation. The drivers of EU and Russian energy policies are evaluated, and the argument advanced is that different understandings of energy security and types of energy governance provide major obstacles to decarbonisation cooperation and trade. However, it is argued that ideas about energy policy and security are contested and subject to change and there exists significant potential for mutual gain and cooperation in the longer term.